A Rapid Array-based Approach to N-glycan Profiling of Cultured Cells - Angel, Peggi M. (J Proteome Res, 2019)
Typically, N-glycosylation studies done on cultured cells require up to millions of cells followed by lengthy preparation to release, isolate, and profile N-glycans. To overcome these limitations, we report a rapid array-based workflow for profiling N-glycan signatures from cells, adapted from imaging mass spectrometry (IMS) used for on-tissue N-glycan profiling. Using this approach, N-glycan profiles from a low-density array of 8 cell chambers could be reported within four hours of completing cell culture. Approaches are demonstrated that account for background N-glycans due to serum media. Normalization procedures are shown. The method is robust and reproducible, requiring as few as 3,000 cells per replicate with 3–20% coefficient of variation to capture label-free profiles of N-glycans. Quantification by stable isotopic labeling of N-glycans in cell culture is demonstrated and adds no additional time to preparation. Utility of the method is demonstrated by measurement of N-glycan turnover rates due to induction of oxidative stress in human primary aortic endothelial cells. The developed method and ancillary tools serve as a foundational launching point for rapid profiling of N-glycans ranging from high-density arrays down to single cells in culture.